1998
DOI: 10.1021/jf9609441
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of “Unfreezable” and “Freezable” Water in Waxy Corn Starch by 2H and 1H NMR

Abstract: "Freezable" and "unfreezable" water in waxy corn starch were characterized by thermal analysis, and the mobility in those states was characterized by solid state (2)H and (1)H NMR. Water was found to be isotropically mobile for samples over a range of water contents (6.3-47% by total weight) at room temperature. Mobility increased with increasing water content and temperature. According to (1)H and (2)H NMR data, a large fraction of "unfreezable" (DSC) was relatively mobile comparable to a liquid state even do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 33 publications
5
75
0
Order By: Relevance
“…In fact, free water molecules, known to be very mobile, can create bonds with other bound water molecules, increasing their mobility. Besides, this interpretation is in agreement with the works of Li et al 12 and Tanner et al, 11 who observed the enhancement of water molecule mobility and a decrease in the residence time for water molecules, respectively, with NMR spectroscopy, independently of the specific limit at 30%. However, because the percentage of bound water does not change above 30% moisture, there is a balance between water molecules creating bonds with starch and other molecules destroying such links.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…In fact, free water molecules, known to be very mobile, can create bonds with other bound water molecules, increasing their mobility. Besides, this interpretation is in agreement with the works of Li et al 12 and Tanner et al, 11 who observed the enhancement of water molecule mobility and a decrease in the residence time for water molecules, respectively, with NMR spectroscopy, independently of the specific limit at 30%. However, because the percentage of bound water does not change above 30% moisture, there is a balance between water molecules creating bonds with starch and other molecules destroying such links.…”
supporting
confidence: 93%
“…The appearance of free water from 30% moisture shows that the polymer may have created all the possible interactions with water, and the water, which is likely to be bound, cannot exceed 33% on a dry basis. This specific limit at MC ϭ 30% was also evoked by Li et al 12 in a study on a waxy corn starch, although they found a slight increase in the bound water content beyond 30% moisture. By carrying out TSC experiments on keratin, which is a protein and not a polysaccharide like starch, Leveque et al 4 noticed a boundary at a water content of 25%, beyond which the intensity of the thermocurrent did not change, whereas the amplitude dropped below 25%.…”
Section: Determination Of Bound and Free Watersupporting
confidence: 69%
See 2 more Smart Citations
“…10 Recently, the approach of combining different analytical techniques has been adopted to better investigate the status of water in several systems. [11][12][13] Differential scanning calorimetry (DSC), and nuclear magnetic resonance (NMR) can offer a different but complementary point of view in studying the water mobility. 11,13,14 The amount of unfreezable water within a sample after being cooled below zero is determined by DSC.…”
Section: Introductionmentioning
confidence: 99%